PERLUKAH UMKM MEMILIKI KEUNGGULAN KOMPETITIF DEMI MEMPERTAHANKAN KEBERLANGSUNGAN USAHANYA? (STUDI KASUS UMKM DI SERANGAN) - Widhiastuti, Ni Luh Putu; Ni Putu Wulan Regina Utami; Sagung Oka Pradnyawati; Kadek Indah Kusuma Dewi; Ni Kadek Nanda Claudia Winyanti (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2024)
The aim of this research is to determine the role of the competitive advantage of MSMEs in maintaining the sustainability of these businesses so that they can still survive today. The research method used is a qualitative approach through interviews with respondents in the hope of directly understanding their managerial actions in creating competitive advantage. The research results show that competitive advantage can be achieved through strengths consisting of a skilled workforce, loyal customers, products that suit consumer tastes, product innovation and strategic location. Opportunities through expanding marketing reach. MSMEs aspirations through collaboration with other parties such as Gojek. The author hopes that these results will be able to provide input for relevant partners in increasing sales with online promotions and maintaining the quality of the production process.